Development of e-sport platform based on virtual reality with functionality - Ho Kim, Yong; Won Bang, Gul (International Journal of Engineering and Technology, 2018)
Background/Objectives: National health promotion through physical activities and expanding social participation as well as improvement of public welfare are emerging as important factors in meeting the needs of the times.Government policy and support measures for invigoratingphysical activities of the disabled and the aged are required in public interest. Therefore the development of e-sport machines combined with interest and its contentsis required as not only an infrastructure of physical activity which is able to be national sports as one man one sport but a new sport core technology.Methods/Statistical analysis: Eco-friendly device is adapted for realizing the sense of power of exercise in consideration of sense of using device like a real play and the effect of exercise. Background and character which reflect sport stadium and participating player to enhance a reality and color is realized. Color design for affective appraisals of the elderly is used.Findings: This study makes it possible not only to measure cognitive dysfunction such as dementia of the aged and memory deterioration but to develop the game which can be improved cognitive function through the measurement but to contribute national health improvement. It will be also considered to be able to secure baseline data in development environment forvirtual reality game product, including kinesthetic sense against the national game industry concentrated in online game. The development of tangible content and interface technology based on physical and psychologicalcondition ofthe aged also makes it possible to use indicator for requiring content in silver industryas well as development of sporting goods.It will be utilized data for the development of the applied technique of realistic content with functionality.Improvements/Applications: The game of sports is further developed after considering physical condition of the each elderly andit is expected to develop popular indoor sports and rehabilitation program.Â